2SPD-030 How to assess the impact of medicines shortages in the European Union?. (23rd March 2022) - Musazzi, U; Di Giorgio, D; Minghetti, P
Abstract : Background and importance: Medicine shortages have been spreading in European countries with a substantial impact on the capability of national healthcare systems to ensure continuity of care. Shortages may originate from unpredictable and multifactorial causes, either supply-related or demand-related. In 2019, the European Medicines Agency (EMA) and Heads of Medicines Agencies (HMA) Joint Task Force released two guidances on shortage notification for manufacturers and communication to the public. 1 However, rational and practical shortage risk-assessment metrics are still needed to support regulators, manufacturers and other healthcare professionals in facing the crisis. 2 Aim and objectives: This work aimed to propose a risk-assessment tool for health professionals, regulatory agencies and other stakeholders to triage shortages' impact on public health. Material and methods: A review of existing metrics and strategies for risk assessment of shortages revealed that most of them are designed to face specific root causes of shortages (eg, manufacturing failures, low price, distribution problem) and cannot be applied to all types. Assuming that shortages' impact should be estimated based on the potential risks of impairing patient accessibility to therapies, relevant criteria have been identified and used to create an algorithm to triage the magnitude of shortages' impact on public health and, therefore, help to define the most appropriate mitigation strategy to be adopted. Results: The designed risk assessment procedure allowed classification of shortages' impact on three levels (high, medium, low) based on three criteria (1) type of disease to be treated, (2) availability of therapeutic alternatives and (3) market shares of the product in a specific European country. 2 Based on the overall score, decision trees for risk-management strategies can be built up for different settings (eg, manufacturers, wholesalers, hospitals, pharmacies) or national regulatory frameworks. Conclusion and relevance: Although further studies in a real-world setting are needed to fully validate the procedure, it is a proof of concept for promoting cooperation and harmonised solutions to medicine shortages. The most critical medicinal products can be selected in advance by competent authorities and stakeholders, improving the resilience of healthcare systems. References and/or acknowledgements: 1. European Medicines Agency. Availability of medicines. https://www.ema.europa.eu/en/human-regulatory/post-authorisation/availability-medicines 2. Musazzi UM, Di Giorgio D, Minghetti P. Int J Pharm 2020;579 :119171. Conflict of interest: No conflict of interest